An adsorptive bioprocess for production and recovery of resveratrol with Corynebacterium glutamicum - Braga, Adelaide (2018)
BACKGROUND The growing interest in polyphenols has led to the design of industrial-scale processes able to produce them by fermentation and recover them in a more sustainable way. The goal of this work is to present two integrated approaches for the recovery of resveratrol, obtained through fermentation. The production of resveratrol using Corynebacterium glutamicum and its continuous removal using a hydrophobic resin is described. Batch production is compared with in situ product removal, where Amberlite XAD-7HP is either directly added to the medium (direct adsorption) or is present in an external column (external adsorption). RESULTS For both adsorption strategies tested, the amount of extracellular resveratrol increased from 75% to at least 90% of the total amount produced. However, lower total resveratrol concentrations were attained 3.6 and 2.2mg L-1, for the external and direct contact strategies, respectively, versus 5.3mg L-1 for batch experiments. CONCLUSIONS The proposed in situ removal strategies demonstrated the potential of increasing the excretion of resveratrol produced intracellularly. These process configurations may not only lead to a simpler downstream process design, but also to the avoidance of potential problems with the toxicity of polyphenols to the cells, especially when larger titers are obtained. © 2017 Society of Chemical Industry